Catalytic ceramic oxygen ionic conducting membrane reactors for ethylene production. Issue 8 (28th May 2021) - Lei, Song; Wang, Ao; Xue, Jian; Wang, Haihui
Abstract : Catalytic ceramic oxygen ionic conducting membrane reactors have great potential in the production of high value-added chemicals as they can couple chemical reactions with separation within a single unit, allowing process intensification. Abstract : Catalytic ceramic oxygen ionic conducting membrane reactors have great potential in the production of high value-added chemicals as they can couple chemical reactions with separation within a single unit, allowing process intensification. This review summarizes the recent progress on catalytic ceramic oxygen ionic conducting membrane reactors in ethylene production; predominantly, the oxidative coupling of methane (OCM) and the oxidative dehydrogenation of ethane (ODE) by thermal catalysis and thermoelectric catalysis are discussed. The influences of oxygen permeability, reaction temperature, the concentration of the reactants, catalysts, and current/voltage on the conversion of reactants and the selectivity of ethylene are discussed in detail. Moreover, the current problems are analyzed and the potential areas for breakthrough are considered. These membrane reactor technologies for ethylene production offer the advantages of energy saving compared with traditional steam cracking, which may provide alternative strategies to achieve green and sustainable chemistry.